PERAN MAHASISWA KKN DALAM MEMBANGUN DESA PEKA (PRODUKTIF, EDUKATIF, KREATIF DAN APLIKATIF) BERSAMA UNIVERSITAS GRESIK - Azhar Rachmad Ramadhan; Reafley Marenjelo P., Ulfa Kurnia Sari, Intan Rohimatul A., Dyah Ayu R., Rahmi Khoironi, Achmad Imad (ADISAM PUBLISHER, 2025)
Sustainable village development in Indonesia requires innovative approaches that integrate aspects of productivity, education, creativity, and practical application. This study aims to analyze the strategic role of KKN students in implementing the PEKA Village concept (Productive, Educational, Creative, and Applicative) through safety and disaster preparedness programs in Betiting Village. The research employed a qualitative approach with field research design, collecting data through in-depth interviews, participatory observation, and documentation analysis using purposive sampling techniques involving village officials, community leaders, and active residents. The results show that KKN students play a strategic role as facilitators in addressing gaps in household safety knowledge that had never previously received attention. The socialization and practical demonstration programs for fire prevention, APAR usage, and LPG safety achieved high effectiveness with 100% participant participation. Success factors include program relevance to real needs, credibility of professional resource persons from the Fire Department, village government support, and interactive methods. The integrated implementation of the four PEKA characteristics successfully increased community capacity in disaster risk mitigation, MSME modernization, and sustainable empowerment. Multi- stakeholder collaboration creates a PEKA Village model that can be replicated for sustainable village transformation based on community participation in Indonesian rural area